PENAMAAN LUBUK - LUBUK DI MEMPAWAH : KAJIAN SEMANTIK - Prayogo, Ricky Muhammad; Amir, Amriani; Jupitasari, Mellisa (Universitas Tanjungpura, 2023)
This study aims to describe the form of naming, and the meaning of naming lubuk - lubuk in Mempawah based on naming lubuk - lubuk in Mempawah: a semantic study. The method used in this study is a descriptive method with a qualitative form. The source of data in this study is the speech of informants who understand the naming of lubuk - lubuk in Mempawah. Data collection techniques are observation techniques, interview techniques, note-taking techniques, and recording techniques. Based on all the data that has been analyzed, there are naming bases that can be classified into six, namely 19 data for naming places based on plants, 10 data for naming places based on people's names, 2 data for naming places based on people's actions, 13 data for naming places based on stories, 2 data for naming places based on geographical conditions, and 1 place naming data based on buildings. The total number of data is 47 data. The form of naming consists of monomorphemic, polymorphemic, and phrase form. Monomorphism in noun form is 14 words, and verb form is 1 word. Polymorphemic in the form of affixation as much as 1 word. Phrases in noun form are 27 words, adjective forms are 1 word, and in verb form are 2 words. The meaning of naming consists of 4 types of meaning, namely lexical meaning there are 24 data, grammatical meaning is 10 data, referential meaning is 7 data, and associative meaning is 1 data.